Analysis of latent class models in economic research - Brzezińska, Justyna (Analiza modeli zmiennych ukrytych w badaniach ekonomicznych, 2016)
Latent variable models are used and applied in many areas of the social and behavioral sciences. The increasing availability of computer packages for fitting such models makes latent variable models popular, known and applied in many scientific areas. Latent variable models have a very wide range of applications, especially in the presence of repeated observations, longitudinal data, and multilevel data. The basic model postulates an underlying categorical latent variable; within any category of the latent variable the manifest or observed categorical variables are assumed independent of one another (the axiom of conditional independence). The observed relationships between the manifest variables are thus assumed to result from the underlying classification of the data produced by the categorical latent variable. In this paper we present the theoretical and methodological aspects of latent variable models, as well as their application in R software in the field of economic research
Ekonometria = Econometrics, 2016, Nr 4 (54), s. 36-47
Keywords: latent class models; latent variables; categorical data analysis; R software; modele klas ukrytych; zmienne ukryte; analiza danych jakościowych; program R